2018
DOI: 10.22153/kej.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bone Defect Animal Model for Hybrid Polymer Matrix Nano Composite as Bone Substitute Biomaterials

Abstract: Addition of bioactive materials such as Titanium oxide (TiO2), and incorporation of bio inert ceramic such as alumina (Al2O3), into polyetheretherketone (PEEK) has been adopted as an effective approach to improve bone-implant interfaces. In this paper, hot pressing technique has been adopted as a production method. This technique gave a homogenous distribution of the additive materials in the proposed composite biomaterial. Different compositions and compounding temperatures have been applied to all samples. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Engineering methods for skeletal muscle tissue regeneration hold promise for treating muscle diseases like muscle dystrophy, traumatic injury, and aggressive tumor ablation. Degradable biomaterials induce new tissue and cell ingrowth, or serve as temporary scaffolds [4][5][6]. The study uses patient's cells or immunologically inactive allogenic or xenogenic cells to engineer tissue scaffolds, potentially replacing lost tissue function and offering new therapeutic options for skin damage in burns.…”
Section: Tissuementioning
confidence: 99%
“…Engineering methods for skeletal muscle tissue regeneration hold promise for treating muscle diseases like muscle dystrophy, traumatic injury, and aggressive tumor ablation. Degradable biomaterials induce new tissue and cell ingrowth, or serve as temporary scaffolds [4][5][6]. The study uses patient's cells or immunologically inactive allogenic or xenogenic cells to engineer tissue scaffolds, potentially replacing lost tissue function and offering new therapeutic options for skin damage in burns.…”
Section: Tissuementioning
confidence: 99%
“…Numerous studies have shown that modifying surfaces with inorganic metal elements such as zinc (Zn), magnesium (Mg), and strontium (Sr) can hasten osseointegration and encourage the formation of new bones [10]. As a result, ceramic oxides or metallic dispersions are used as reinforcing agents [11]. Sr is thought to have multiple action mechanisms.…”
Section: Introductionmentioning
confidence: 99%